Chinese SLE Treatment and Research Group Registry (CSTAR) XIV: the subjective well-being of patients with systemic lupus erythematosus - Shi, Yue; Bi, Dandan; Wang, Yanhong; Li, Ruofan; Wu, Lijun; Zhao, Cheng; Wu, Zhenbiao; Duan, Xinwang; Xu, Jian; Zhan, Feng; Yang, Min; Liu, Shengyun; et al. (Frontiers in Medicine, 2022)
Background Systemic lupus erythematosus (SLE) can significantly influence patients’ quality of life and subjective well-being (SWB), but the relationships between clinical characteristics, SWB, and related psychological factors have been little studied. Objective To measure SWB in patients with SLE and examine how major clinical determinants, emotional variables, and related positive factors affect SWB. Methods Overall, 1,110 patients with SLE from the Chinese SLE Treatment and Research Group (CSTAR) and 198 age and gender-matched individuals from the general population without self-reported SLE were invited to complete questionnaires of SWB evaluated by the satisfaction with life scale (SWLS), emotional variables assessed by the patient health questionnaire-9 (PHQ-9), and general anxiety disorder-7 (GAD-7) and related positive factors assessed by the self-esteem scale (SES), general self-efficacy scale (GESE), and Connor-Davidson resilience scale (CD-RISC). The multivariate linear regression was used to examine the relationship between clinical manifestations and SWB. Results Life satisfaction was significantly lower (p < 0.001) in patients with SLE than in the general population. Active skin involvement (OR = 0.923, 95% CI = 0.868–0.981, p < 0.05) was negatively associated with life satisfaction scores, and age at enrollment (OR = 1.160, 95% CI = 1.092–1.230, p < 0.001) were positively associated with life satisfaction scores in the multivariate regression model. The cumulative organ damage was significantly associated with depression (OR = 1.085, 95% CI = 1.022–1.153, p < 0.01) and the loss of self-esteem (OR = 1.067, 95% CI = 1.004–1.133, p < 0.05). Conclusion SWB provides useful insight into the impact of SLE on psychological health and opportunities to improve quality of life and clinical care.